2021
DOI: 10.1021/acs.nanolett.1c01419
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Dynamic Camouflage from Colloidal Nanocrystals Embedded Electrochromics

Abstract: Camouflage is often seen in animals, and it presents in both passive and active forms. For instance, the wings of Closterocerus coffeellae exhibit distinct appearances against different backgrounds, while the chameleon actively changes its skin colors to morph into the environment. Herein, we report an artificial skin-like optoelectronic device that enables actively changing appearances and passively morphing into the environment by manipulating light–matter interactions with electrochromic polymers and photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…An interesting artificial skin-like camouflage material was very recently reported. It is a multi-component hybrid system consisting of green photonic nanocrystals embedded into a gel electrolyte and assembled between the layer of the EC polymer and an ion-storage layer . As a result, the device demonstrated chameleon-like properties: active change of appearance due to the voltage-controlled EC color change and passive morphing into the environment that depends on the structural background and viewing angles.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting artificial skin-like camouflage material was very recently reported. It is a multi-component hybrid system consisting of green photonic nanocrystals embedded into a gel electrolyte and assembled between the layer of the EC polymer and an ion-storage layer . As a result, the device demonstrated chameleon-like properties: active change of appearance due to the voltage-controlled EC color change and passive morphing into the environment that depends on the structural background and viewing angles.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom: the color appearance/disappearance of the butterfly device for both active and passive camouflage. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Electrochromic Materials and Devicesmentioning
confidence: 99%
“…Introducing related physical structures to electrolytes can also achieve this goal. For example, Jianguo Mei’s research group reported colloidal nanocrystal (containing SiO 2 nanoparticles) embedded electrolytes in electrochromics . In their work, the as-prepared electrolytes achieved passive structural-color change according to the background colors (e.g., marble or white backgrounds).…”
Section: Electrochromic Materials and Devicesmentioning
confidence: 99%
“…[1][2][3][4][5] The reversible color change is induced by electrochemical oxidation and reduction reactions. Several electrochromic devices have been developed for various commercial applications, such as optical sensors, [6] electronic tags, [7] color displays, [8] mirrors, [9] camouflage, [10] and smart windows. [11][12][13] Amongst the electrochromic devices, those that incorporate plasmonic nanomaterials are by at a low voltage, where metal adatoms and adlayers are formed on the solid substrate at a potential that is positive relative to the metal's equilibrium (i.e., Nernst) reduction potential.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] The reversible color change is induced by electrochemical oxidation and reduction reactions. Several electrochromic devices have been developed for various commercial applications, such as optical sensors, [ 6 ] electronic tags, [ 7 ] color displays, [ 8 ] mirrors, [ 9 ] camouflage, [ 10 ] and smart windows. [ 11–13 ] Amongst the electrochromic devices, those that incorporate plasmonic nanomaterials are by far the most intriguing.…”
Section: Introductionmentioning
confidence: 99%